Slot-die coating of perovskite solar cells: An overview. (March 2020) - Patidar, Rahul; Burkitt, Daniel; Hooper, Katherine; Richards, David; Watson, Trystan
Abstract : Graphical abstract: Abstract: To make perovskite solar cells an industrially relevant technology large area deposition techniques are needed and one of the most promising is slot-die coating. This review article details the progress reported in the literature where slot-die coating has been used for the deposition of both the perovskite layer and other layers in the perovskite solar cell device stack. An overview of the methods used to adapt the coating process, materials and drying conditions in order to create high quality layers and devices is given and an outlook on future research directions in this field is made.